Development of a blood test for uterine sarcoma—Diagnosis and monitoring (DOORS-D and DOORS-M) studies - Anna Casey; Rebecca Allsopp; Jacqui Shaw; Caroline Cowley; Elizabeth Stannard; Yvette Griffin; Indrajeet Das; Marc Wadsley; Natalie Darko; Esther L. Moss (PLoS ONE, 2026)
Uterine sarcomas can be difficult to differentiate from uterine fibroids due to many shared symptoms and imaging features, which can result in delayed or missed diagnosis, or over treatment. The ‘Development of a blood test for uterine Sarcoma – Diagnosis’ (DOORS-D) (ISRCTN14800787) and ‘Development of a blood test for uterine Sarcoma – Monitoring’ (DOORS-M) (ISRCTN14174468) studies aim to explore the role for circulating tumour DNA (ctDNA) to diagnose and to monitor uterine sarcomas. DOORS-D will recruit patients who have a suspected uterine sarcoma or large fibroid and are due to undergo surgery (hysterectomy or myomectomy) for a blood sample prior to surgery whereas DOORS-M will recruit patients who have been diagnosed with a uterine sarcoma in the previous 10 years for longitudinal blood sampling every 3–6 months over the course of the study. Information will be collated on patient characteristics and symptoms, tumour characteristics and diagnostic imaging, with representative images selected and analysed using large language models. Analysis of genomic/methylation profile of ctDNA samples collected from DOORS-M will be used to design a ctDNA-based ‘test’. Analysis of the samples collected from the participants recruited to the DOORS-D study will enable the accuracy of the ‘test’ to differentiate uterine sarcomas from fibroids to be determined. In addition, the opinions of patients with a suspected or confirmed sarcoma will be explored through semi-structured qualitative interviews. Purposeful recruitment strategy will ensure that the experiences of women from diverse socioeconomic, cultural and ethnic backgrounds are included. The results of the studies will be shared through conference presentations and peer-reviewed publications.